Synthesis of a fluorophore for the investigation of the biosynthesis of glycosaminoglycans - Oudeh,Adnan (2026)
Inside the human body, cells produce long sugar chains called glycosaminoglycans, or named shortly as GAGs, these sugars play an important role in our body since they are involved in important biological processes such as blood coagulation, being components in our cartilage, and the new development of tissues. Changes in these sugars is associated with several diseases such as in some kinds of cancer and metastasis. Even though the enzymes that form GAGs are known, it is still not fully understood where these are located inside the cell and how this process can be selective in producing certain GAGs for certain types of tissues. One way to study how these sugars are made is to use small synthetic molecules that can enter cells and initiate GAG production. By attaching a fluorescent dye to such a molecule, it may be possible to follow the biosynthesis visually using microscopy. However, earlier fluorescent probes have often failed to fully trace the process because the fluorescent dyes carry electrical charges that interfere with normal transport inside the cell, causing the molecule to be ejected before fully visualizing the synthesis. The aim of this thesis was to synthesise a new fluorescent molecule designed to reduce these limitations. The project focused on the synthesis of a sugar-based compound linked to a modified fluorescent dye with a lower electrical charge than the previous attempts, with the goal of improving its compatibility with the cellular environment. Conventional organic chemistry techniques were used to build the molecule, and analytical methods were applied to confirm the structures of the synthesized compounds. Although the final target molecule could not be fully synthesized within the scope of this project, several important intermediate compounds were successfully prepared, and key challenges in the synthetic route were identified.
Keywords: Bioorganic chemistry; Organic chemistry; Glycosaminoglyacans; Carbohydrates